The effect of vegetation cover on dust concentration: Case study (Constantine, Algeria) - Maya Benoumeldjadj; Nedjoua Bouarroudj; Abdelouahab Bouchareb (Indonesian Journal of Geography, 2023)
Even though urban greenery is crucial in maintaining a healthy and pollution-free environment, metropolitan areas are facing a significant threat from pollution, particularly dust particles. Therefore, this study used the advanced remote sensing techniques to explore the relationship between dust concentration and vegetation cover in Constantine, Algeria. As urban development continues to encroach upon green spaces, pollution, especially dust particles, has emerged as a pressing concern in metropolitan areas. This study used data from USGS and GLOvis for climate analysis, while Landsat images from GEE were employed for accurate mapping. Multiple years of comprehensive datasets were collected, including land cover maps, Aridity Index (AI), precipitation data, and Normalized Difference Vegetation Index (NDVI) maps, which underwent thorough analysis. NDVI and Dust Index (DI) were employed to evaluate the impact of vegetation on dust concentration. The result showed that the presence of vegetation directly affects dust levels, and DI exhibits variations over time in relation to the values of NDVI. This study highlights the critical significance of preserving and enhancing urban greenery to mitigate dust pollution and foster a healthier environment.